2023
DOI: 10.22201/fca.24488410e.2023.3426
|View full text |Cite
|
Sign up to set email alerts
|

Health awareness determines the consumer purchase intention towards herbal products and risk as moderator

Abstract: <h1>Consumer interest in herbal products is an interesting topic related to the choice of a healthy lifestyle. The trend in consumer demand for herbal products has increased in recent years. During this pandemic, the demand for herbal products is getting higher. Herbal products are widely used for individual health care or alternative medicine. This study aims to obtain an objective behavioral study of consumer interest in herbal products. We further explore how risk moderates the relationship between he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, the relationship between health consciousness and customers' purchase intentions toward herbal products and supplements is still divergent. In general, previous research has found that health consciousness has positive and significant effect on customers' purchase intention toward herbal products, supplements, and organic and green products (Widyaningtyas et al, 2023;Handayani & Darmawan, 2022;Wahab & Tajuddin, 2020;Parashar et al, 2023;Damberg, 2022;Shah et al, 2021;Tan et al, 2019). Meanwhile, some researchers fail to find the significant effect of health consciousness on customers' purchase intention toward herbal products, supplements, and organic and green products (Sultan et al, 2019;Asteria & Hati, 2023;Echchad, 2023).…”
Section: Introductionmentioning
confidence: 98%
“…However, the relationship between health consciousness and customers' purchase intentions toward herbal products and supplements is still divergent. In general, previous research has found that health consciousness has positive and significant effect on customers' purchase intention toward herbal products, supplements, and organic and green products (Widyaningtyas et al, 2023;Handayani & Darmawan, 2022;Wahab & Tajuddin, 2020;Parashar et al, 2023;Damberg, 2022;Shah et al, 2021;Tan et al, 2019). Meanwhile, some researchers fail to find the significant effect of health consciousness on customers' purchase intention toward herbal products, supplements, and organic and green products (Sultan et al, 2019;Asteria & Hati, 2023;Echchad, 2023).…”
Section: Introductionmentioning
confidence: 98%